Preferences need no inferences, once again: Germinal elements in the public perceptions of genetically modified foods in Colombia (2004)
This paper explores the public perceptions of genetically modified foods in Colombia in a phase considered germinal: the topic was too novel at the time of research. The analysis covers media, informal conversations, and the word associations made by a sample of residents in the city of Bogota. The results show that the public capability of associating with the topic, even intuitively, is due to the availability of cultural themes, the primary categories that help conceptual elaborations, and the construction of common-sense theories. Three themes are proposed: natural/artificial, tradition/change, and health/disease. It is argued that cultural themes are not only cognitive, but also affectively laden entities, which explains the evaluative force expressed by social beliefs. Acknowledging the relevance of the non-attitude thesis, the author suggests that people associate novel objects with latent cultural meanings, explaining why words, images, and metaphors are readily available in elaborating social knowledge.